Prevalensi Terjadinya Komplikasi pada Ibu Hamil dengan Infeksi Covid-19 Post Sectio Caesarea - Utami, Nadila Rizqi; Herdiyantini, Mita; Budiarti, Retno; Harnanik, Titut (Jurnal Kesehatan, 2024)
Pregnancy is a period of fetal growth and development accompanied by physiological and immunological changes in the mother, making her more susceptible to infections, including COVID-19. Pregnancy accompanied by COVID-19 infection increases the risk of complications for pregnant women. This study aims to determine the prevalence of post-Caesarean section complications in pregnant women with COVID-19. The sampling method employed purposive sampling by observing medical record data at Dr. Ramelan Surabaya Hospital during the period from March 2020 to March 2023. Out of a total of 100 samples, there were 58 confirmed cases of COVID-19, with 8 cases (32.0%) of cardiovascular complications, consisting of 6 cases (75.0%) of PPH complications, and 2 cases (25.0%) of surgical wound infection complications. The prevalence of respiratory system complications included 13 cases (52.0%), with 9 cases (69.2%) of pneumonia complications and 4 cases (30.8%) of Acute Respiratory Distress Syndrome complications. One case (4.0%) of sepsis and 3 cases (12.0%) of maternal death complications were identified. The results of the data analysis using the Contingency Coefficient test showed a p-value of 0.001 (p < α), indicating a significant relationship between COVID-19 infection and an increased prevalence of complications in pregnant women. In conclusion, the study found 25 cases (43.1%) of post-Caesarean section complications in pregnant women with COVID-19, indicating an increased prevalence of complications in pregnant women with COVID-19 post-Caesarean section.